2022
DOI: 10.1245/s10434-021-11010-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgical Margins on Overall Survival after Gastrectomy for Gastric Cancer: A Validation of Japanese Gastric Cancer Association Guidelines on a Western Series

Abstract: Purpose No consensus exists on the resection extent needed to ensure oncological safety in gastrectomy for gastric adenocarcinoma (GAC). This study aims to assess the impact of margin adequacy according to Japanese Gastric Cancer Association (JGCA) guidelines on overall survival (OS). Patients and Methods Patients who underwent surgery for stage I–III GAC at our institution between 2010 and 2017 were included. Margin adequacy according to JGCA, National Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Subtotal gastrectomy can be selected when a satisfactory proximal resection margin can be obtained. [58][59][60] The extent of nodal dissection accompanying radical gastrectomy has been extensively debated. D1 resection implies removal of the perigastric lymph nodes plus those along the left gastric artery.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Subtotal gastrectomy can be selected when a satisfactory proximal resection margin can be obtained. [58][59][60] The extent of nodal dissection accompanying radical gastrectomy has been extensively debated. D1 resection implies removal of the perigastric lymph nodes plus those along the left gastric artery.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In the current version of the guidelines, the recommendation was adapted to the recommendations of the Asian guidelines by requiring proximal margins of at least 3 cm for tumours with an expansive growth pattern and at least 5 cm for tumours with an infiltrative growth pattern [ 10 ]. The changes made to European recommendations are the result of an Italian study that validated the minimal resection margins required by the Japanese guidelines on a Western patient population [ 65 •]. In this study, compliance with the Japanese recommendations for resection margins was independently associated with overall survival.…”
Section: Standard Resection Proceduresmentioning
confidence: 76%
“…Despite the aforementioned guidelines, several authors highlighted the absence of any significant influence of proximal margin length on GC overall survival [ 36 , 37 , 38 , 39 ], unlike others which advocated for a patient-tailored proximal margin length as an independent prognostic factor [ 40 ]. Recently, Maspero et al assessed the impact of JGCA-recommended resection margins on long-term outcomes of 279 consecutive Western patients [ 41 ]. Analyzing 220 distal gastrectomies, the authors found that application of JGCA guidelines resulted in improved overall survival and a more organ-preserving surgical strategy, owing to a significant lower number of total gastrectomies compared with NCCN and ESMO guidelines (30% vs. 31% vs. 47%, respectively) without compromising oncological outcomes [ 41 ].…”
Section: Non-metastatic Gastric Cancermentioning
confidence: 99%
“…Recently, Maspero et al assessed the impact of JGCA-recommended resection margins on long-term outcomes of 279 consecutive Western patients [ 41 ]. Analyzing 220 distal gastrectomies, the authors found that application of JGCA guidelines resulted in improved overall survival and a more organ-preserving surgical strategy, owing to a significant lower number of total gastrectomies compared with NCCN and ESMO guidelines (30% vs. 31% vs. 47%, respectively) without compromising oncological outcomes [ 41 ].…”
Section: Non-metastatic Gastric Cancermentioning
confidence: 99%